Pengaruh Variasi Metode Pembelajaran dan Bimbingan Keluarga Terhadap Hasil Belajar PAK & Budi Pekerti Siswa Kelas XI SMA Swasta Parsaoran - Fernando Tinambunan (IAKN Tarutung, 2022)
This research aims to know the Effect of Variations in Learning Methods and Family’s Guidance on students’ Learning Achievement for Christian Education of Class XI in the SMA Swasta Parsaoran. This research used a quantitative approach with descriptive inferential data analysis, with the population of all the students of Class XI in SMA Swasta Parsaoran consists of 117 students and it was taken 30 students as a sample of the research similar with 26% population. The instrument of the research was closed questionnaires which of the arranged by the researcher. The tryout was done for 30 students out of the was sample of the research. The number of the questionnaires items were 60 of which 40 item for variable x and 20 items for variable y, and the result showed good validity and reliability. The result of research analysis, concluded: 1) there were positive and significant effect of variations in learning methods on student learning Achievement for Christian education, 2) there were positive and significant effect of family’s guidance on student learning Achievement for Christian education, 3) there were positive and significant effect Variations in Learning Methods and Family’s Guidance on student’s Learning Achievement for Christian Education. It means, that to increase students’ learning Achievement for Christian Education, the Variations in Learning Methods and Family’s Guidance need to be improved